Effect of Si/Zr molar ratio on the sintering and crystallization behavior of zircon ceramics. Issue 13 (October 2020) - Jiang, Zhengdi; Xiong, Tianheng; Bai, Zimei; Zhao, Dandan; Yang, Wenping; Peng, Yun; Dan, Hui; Ding, Yi; Duan, Tao
Highlights: x SiO2 /ZrSiO4 ceramics were prepared using SiO2 and ZrO2 as raw materials. Effect of Si/Zr molar ratio on the phase and microstructure evolutions was studied. Formation rate of Zircon phase was strongly affected by the Si/Zr molar ratio. Phase and microstructure evolutions were affected by sintering temperature. The compactness of zircon ceramics can be enhanced by increasing Si/Zr molar ratio. Abstract: Zircon (ZrSiO4 ) ceramics have been widely used in the field of radioactive waste immobilization and ceramics industry. However, preparation of zircon ceramics suffers from low yield due to the variable Si/Zr molar ratio. Herein, we reported preparation of x SiO2 /ZrSiO4 (0 ≤ x ≤ 0.3) ceramics using SiO2 and ZrO2 as raw materials. The effects of Si/Zr molar ratio and sintering temperature on the phase formation, phase and microstructure evolutions were investigated. The results indicated that zircon formation efficiency increased with increasing Si/Zr molar ratio from 1 to 1.2, while decreased with increasing Si/Zr molar ratio from 1.2 to 1.3. The as-prepared ceramics with Si/Zr molar ratio of 1.1 and 1.2 were single zircon phase, while with Si/Zr molar ratio of 1 and 1.3 exhibited coexistence of zircon and cristobalite phases. The grain growth and compactness can be enhanced by increasing Si/Zr molar ratio. Furthermore, the relative densities increased with increasing Si/Zr molar ratio.